Combining ultrasonic and computed tomography scanning to characterize mechanical properties of cancellous bone in necrotic human femoral heads. (April 2019) - Yue, Yue; Yang, Haisheng; Li, Yan; Zhong, Honggang; Tang, Qi; Wang, Jiantong; Wang, Rongtian; He, Haijun; Chen, Weiheng; Chen, Duanduan
Highlights: This experiment is carried out based on patients with femoral head necrosis. The accuracy of the experiment is at millimeter level. This study mainly determined the relationship between density and elastic modulus for the entire femoral head. The material properties of necrotic femoral heads and normal femoral heads are measured in this experiment using ultrasound scanning combined with CT scanning. Abstract: Image-based finite element modelling has been commonly used to determine the biomechanical behaviours of human femora, particularly for the diagnosis of femoral head necrosis. One of the fundamental aspects of biomechanical modelling is the relationship between bone density, which is obtained from images, and elastic modulus. While there exist some empirical equations relating density with elastic modulus, the characterization of this relationship remains incomplete, especially for necrotic femoral heads. The objective of this study was to determine the relationship between density and elastic modulus by combining ultrasonic scanning and computed tomography (CT). Bone specimens were surgically removed from the femora of eight persons (seven females and one male in the age range of 55–68 years old) and underwent both ultrasonic and CT scanning. The images were processed with MATLAB scripts, and a bilinear interpolation algorithm was used to determine the relationship between the CT-measured densities and ultrasound-measured elastic moduli. The results showed different density–elastic modulus relations between the hardening strap of the necrotic region and non-hardening strap areas of the necrotic region. The uniqueness of this study is the characterization of mechanical properties (in the present study, the density–modulus relationship) from clinical images, which would be valuable in computational biomechanics used for the diagnosis and treatment evaluation of femoral head necrosis.